Host‐associated bacterial community succession during amphibian development. Issue 8 (23rd March 2018) - Prest, Tiffany L.; Kimball, Abigail K.; Kueneman, Jordan G.; McKenzie, Valerie J.
Abstract: Amphibians undergo significant developmental changes during their life cycle, as they typically move from a primarily aquatic environment to a more terrestrial one. Amphibian skin is a mucosal tissue that assembles communities of symbiotic microbiota. However, it is currently not well understood as to where amphibians acquire their skin symbionts, and whether the sources of microbial symbionts change throughout development. In this study, we utilized data collected from four wild boreal toad populations ( Anaxyrus boreas ); specifically, we sampled the skin bacterial communities during toad development, including eggs, tadpoles, subadults and adults as well as environmental sources of bacteria (water, aquatic sediment and soil). Using 16S rRNA marker gene profiling coupled with SourceTracker, we show that while primary environmental sources remained constant throughout the life cycle, secondary sources of boreal toad symbionts significantly changed with development. We found that toad skin communities changed predictably across development and that two developmental disturbance events (egg hatching and metamorphosis) dictated major changes. Toad skin communities assembled to alternative stable states following each of these developmental disturbances. Using the predicted average rRNA operon copy number of the communities at each life stage, we showed how the skin bacterial communities undergo a successional pattern whereby "fast‐growing" (copiotroph) generalist bacteria dominate first before "slow‐growing" (oligotroph) specialized bacteria take over. Our study highlights how host‐associated bacterial community assembly is tightly coupled to host development and that host‐associated communities demonstrate successional patterns akin to those observed in free‐living bacteria as well as macrofaunal communities.